SnSeS / carbon composite material and preparation method thereof, and sodium ion battery

CN120398034BActive Publication Date: 2026-10-30HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510566419.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30
Estimated Expiration
2045-04-30

AI Technical Summary

Technical Problem

然而,由于其电子/离子电导率不理想,结构降解和体积变化严重,SnSeS在充放电过程中表现出动力学缺陷和容量衰减快的问题

Benefits of technology

[0011]本发明实施例的SnSeS/碳复合材料的制备方法带来的优点和技术效果:通过机械球磨工艺制备锡基炭复合前驱体,经过热处理高温退火、再次热处理气相硒硫化得到SnSeS/碳复合材料(SnSeS/C)。具体地,球磨工艺是实现纳米复合化的核心技术手段,通过机械力作用将锡盐和碳源在纳米尺度上均匀复合,形成具有协同效应的纳米复合材料,为后续高温处理过程中三维碳框架结构的形成提供结构基础和均匀分散的前驱体。球磨促进锡基材料与碳材料的均匀分散,形成纳米复合结构,避免局部团聚。在球磨中引入碳源,一方面在高温处理的过程中促交联三维碳框架的形成,纳米复合化缩短SnSeS内部的电子/离子传输路径以及提供外部的电子快速传输通道来加快电极反应动力学,提供更多的活性位点,从而得到具有优异倍率性能和较长循环寿命的SnSeS/碳复合材料,适用于钠离子电池负极材料;另一方面发现在球磨过程中加入碳源能够减少活性颗粒团聚。前驱体热处理促进锡基材料与炭材料的相互作用,优化锡基材料的晶体结构和微观形貌。中间产物热处理进行气相硒硫化,形成SnSeS相,得到SnSeS/碳复合材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398034B_ABST
    Figure CN120398034B_ABST
Patent Text Reader

Abstract

The application discloses a SnSeS / carbon composite material and a preparation method and a sodium ion battery thereof. The preparation method of the SnSeS / carbon composite material comprises the following steps: mixing, ball-milling and mixing a tin salt, a carbon source and a solvent to obtain a precursor; performing heat treatment on the precursor in an inert atmosphere to obtain an intermediate product; and performing heat treatment on the intermediate product and a sulfur source and a selenium source in the inert atmosphere to obtain the SnSeS / carbon composite material. The SnSeS / carbon composite material prepared by the method has a three-dimensional carbon frame structure and SnSeS nanoparticles are distributed in the interior and on the surface of the SnSeS / carbon composite material, and the SnSeS / carbon composite material has excellent rate performance and a long cycle life, and can be used as a negative electrode material of a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion batteries, and more specifically, to a SnSeS / carbon composite material, its preparation method, and a sodium-ion battery. Background Technology

[0002] Sodium is abundant and inexpensive on Earth, leading to rapidly growing market demand for sodium-ion batteries. Electrode materials account for approximately 70% of the total cost of sodium-ion batteries, making the development of electrode materials with excellent electrochemical performance crucial. The power density and cycle life of batteries are limited by the slow reaction kinetics of the negative electrode; therefore, the development of novel high-capacity negative electrode materials is of great significance for promoting the application of sodium-ion batteries.

[0003] Ternary tin-based chalcogenides (SnSeS) offer high theoretical capacities based on various ion storage mechanisms and suitable voltage platforms. Their layered structure with large interlayer spacing is conducive to the insertion of alkali metal (Li, Na, K) ions. However, due to their non-ideal electronic / ionic conductivity, severe structural degradation, and volume changes, SnSeS exhibits kinetic defects and rapid capacity decay during charge and discharge processes.

[0004] Currently, the main methods for preparing chalcogenide / carbon composite materials are hydrothermal synthesis and coprecipitation. However, these two methods require harsh reaction conditions, are time-consuming, cause significant environmental pollution, and have low yields. Therefore, there is a need to explore a simple, efficient, and environmentally friendly synthesis method to prepare electrode materials with high specific capacity. Summary of the Invention

[0005] This invention is based on the inventors' discoveries and understanding of the following facts and problems: Due to the unsatisfactory electronic / ionic conductivity of SnSeS, its structure degrades and volume changes severely, leading to kinetic defects and rapid capacity decay during charge and discharge. Current methods for preparing chalcogenide / carbon composite materials mainly rely on hydrothermal and coprecipitation methods, which involve harsh reaction conditions, long processing times, significant environmental pollution, and low yields.

[0006] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention propose a SnSeS / carbon composite material and its preparation method, as well as a sodium-ion battery. The SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and long cycle life, and can be used as a negative electrode material for sodium-ion batteries.

[0007] This invention provides a method for preparing SnSeS / carbon composite materials, comprising the following steps:

[0008] (1) The tin salt, carbon source and solvent are mixed and ball-milled to obtain the precursor;

[0009] (2) The precursor is heat-treated in an inert atmosphere to obtain an intermediate product;

[0010] (3) The intermediate product is heat-treated with a sulfur source and a selenium source under an inert atmosphere to obtain a SnSeS / carbon composite material.

[0011] The advantages and technical effects of the SnSeS / carbon composite material preparation method of this invention are as follows: A tin-based carbon composite precursor is prepared by mechanical ball milling, followed by high-temperature annealing and a second heat treatment with gas-phase selenium sulfidation to obtain the SnSeS / carbon composite material (SnSeS / C). Specifically, ball milling is the core technology for achieving nanocomposite formation. Through mechanical force, tin salt and carbon source are uniformly composited at the nanoscale, forming a nanocomposite material with synergistic effects. This provides a structural basis and a uniformly dispersed precursor for the formation of a three-dimensional carbon framework during subsequent high-temperature treatment. Ball milling promotes the uniform dispersion of tin-based and carbon materials, forming a nanocomposite structure and avoiding local agglomeration. Introducing a carbon source during ball milling promotes the formation of a cross-linked three-dimensional carbon framework during high-temperature treatment. Nanocomposite formation shortens the electron / ion transport path within SnSeS and provides a fast external electron transport channel to accelerate electrode reaction kinetics, providing more active sites. This results in a SnSeS / carbon composite material with excellent rate performance and long cycle life, suitable for sodium-ion battery anode materials. Furthermore, it has been found that adding a carbon source during ball milling reduces the agglomeration of active particles. Precursor heat treatment promotes the interaction between tin-based and carbon materials, optimizing the crystal structure and microstructure of the tin-based material. The intermediate product undergoes heat treatment followed by gas-phase selenium sulfidation to form the SnSeS phase, yielding the SnSeS / carbon composite material.

[0012] In this embodiment of the invention, the SnSeS / carbon composite material uses a ternary tin-based chalcogenide (SnSeS), which provides a high theoretical capacity based on multiple ion storage mechanisms and an appropriate voltage platform. Its layered structure with large interlayer spacing is conducive to the insertion and storage of alkali (Li, Na, K) ions. The method of this invention combines nanostructured SnSeS with carbon, accelerating electrode reaction kinetics by shortening the electron / ion transport path inside SnSeS and providing an external fast electron transport channel. The SnSeS / carbon composite material exhibits excellent rate performance and long cycle life, and can be used as a negative electrode material for sodium-ion batteries.

[0013] In this embodiment of the invention, the method is simple to operate, environmentally friendly, and yields high output. The tin-based precursor prepared by the mechanochemical method effectively avoids the problems of long synthesis time and large solvent requirements of traditional co-precipitation and hydrothermal methods. The synthesis process is simple, efficient, scalable, and suitable for large-scale industrial production.

[0014] In some embodiments, in step (1), the tin salt includes at least one of tin oxalate, tin chloride, and tin sulfate;

[0015] And / or, the carbon source includes at least one of coconut shell charcoal, rice husk charcoal, and straw charcoal;

[0016] And / or, the molar amount of the tin salt to the mass ratio of the carbon source is (1-5 mmol): (1-5 g);

[0017] And / or, the solvent includes at least one of water, ethanol, or N,N-dimethylformamide.

[0018] In some embodiments, during step (1), the total mass ratio of the tin salt and carbon source to the mass of the milling beads is 1:(2-60).

[0019] And / or, the ball milling time is 1 to 20 hours;

[0020] And / or, the ball mill rotates at a speed of 200 to 600 rpm.

[0021] In some embodiments, in step (2), the inert atmosphere includes at least one of nitrogen or argon;

[0022] And / or, the temperature of the heat treatment is 400–1000°C;

[0023] And / or, the heat treatment holding time is 1 to 5 hours.

[0024] In some embodiments, in step (3), the selenium source includes at least one of selenium powder and selenium dioxide;

[0025] And / or, the sulfur source includes at least one of sulfur powder, thiourea, and thioacetamide;

[0026] And / or, the mass ratio of the intermediate product to the sulfur source and the selenium source is 1:(2-5):(2-5);

[0027] And / or, the temperature of the heat treatment is 300–600°C;

[0028] And / or, the heat treatment holding time is 1 to 3 hours;

[0029] And / or, the inert atmosphere includes at least one of nitrogen or argon.

[0030] In some embodiments, in step (3), the SnSeS / carbon composite material has a three-dimensional carbon framework structure, and SnSeS particles are distributed inside and on the surface of the three-dimensional carbon framework structure; the particle size of the SnSeS particles is 20-50 nm.

[0031] This invention provides a SnSeS / carbon composite material, which is prepared using the method described in this invention. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and a long cycle life.

[0032] This invention provides an application of a SnSeS / carbon composite material for sodium-ion batteries. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and long cycle life, and can be used as a negative electrode material for sodium-ion batteries.

[0033] This invention provides an anode material, including the SnSeS / carbon composite material described in this embodiment. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and long cycle life, and can be used as an anode material.

[0034] This invention provides a sodium-ion battery comprising the SnSeS / carbon composite material described in this embodiment. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on its surface, exhibiting excellent rate performance and long cycle life, and can be used in sodium-ion batteries. Attached Figure Description

[0035] Figure 1 These are scanning electron microscope (SEM) images of SnSeS / C prepared in Example 1 at different magnifications.

[0036] Figure 2 This is the X-ray diffraction (XRD) pattern of SnSeS / C prepared in Example 1.

[0037] Figure 3 The battery cycle performance is that of the SnSeS / C composite material prepared in Example 1.

[0038] Figure 4 This refers to the battery rate performance of the SnSeS / C composite material prepared in Example 1. Detailed Implementation

[0039] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0040] A method for preparing a SnSeS / carbon composite material according to an embodiment of the present invention includes:

[0041] (1) The tin salt, carbon source and solvent are mixed and ball-milled to obtain the precursor;

[0042] (2) The precursor is heat-treated in an inert atmosphere to obtain an intermediate product;

[0043] (3) The intermediate product is heat-treated with a sulfur source and a selenium source under an inert atmosphere to obtain a SnSeS / carbon composite material.

[0044] The method for preparing SnSeS / carbon composite material according to this invention involves preparing a tin-based carbon composite precursor through mechanical ball milling, followed by high-temperature annealing and a second heat treatment with gas-phase selenium sulfidation to obtain the SnSeS / carbon composite material (SnSeS / C). Specifically, ball milling is the core technology for achieving nanocomposite formation. Through mechanical force, tin salt and carbon source are uniformly composited at the nanoscale, forming a nanocomposite material with synergistic effects. This provides a structural basis and a uniformly dispersed precursor for the formation of a three-dimensional carbon framework during subsequent high-temperature treatment. Ball milling promotes the uniform dispersion of tin-based and carbon materials, forming a nanocomposite structure and avoiding local agglomeration. Introducing a carbon source during ball milling promotes the formation of a cross-linked three-dimensional carbon framework during high-temperature treatment. Nanocomposite formation shortens the electron / ion transport path within SnSeS and provides external fast electron transport channels to accelerate electrode reaction kinetics, providing more active sites. This results in a SnSeS / carbon composite material with excellent rate performance and long cycle life, suitable for sodium-ion battery anode materials. Furthermore, it has been found that adding a carbon source during ball milling reduces the agglomeration of active particles. Precursor heat treatment promotes the interaction between tin-based and carbon materials, optimizing the crystal structure and microstructure of the tin-based material. The intermediate product undergoes heat treatment followed by gas-phase selenium sulfidation to form the SnSeS phase, yielding the SnSeS / carbon composite material.

[0045] In this embodiment of the invention, the SnSeS / carbon composite material uses a ternary tin-based chalcogenide (SnSeS), which provides a high theoretical capacity based on multiple ion storage mechanisms and an appropriate voltage platform. Its layered structure with large interlayer spacing is conducive to the insertion and storage of alkali (Li, Na, K) ions. The method of this invention combines nanostructured SnSeS with carbon, accelerating electrode reaction kinetics by shortening the electron / ion transport path inside SnSeS and providing an external fast electron transport channel. The SnSeS / carbon composite material exhibits excellent rate performance and long cycle life, and can be used as a negative electrode material for sodium-ion batteries.

[0046] In this embodiment of the invention, the method is simple to operate, environmentally friendly, and yields high output. The tin-based precursor prepared by the mechanochemical method effectively avoids the problems of long synthesis time and large solvent requirements of traditional co-precipitation and hydrothermal methods. The synthesis process is simple, efficient, scalable, and suitable for large-scale industrial production.

[0047] In some embodiments, in step (1), the tin salt includes at least one of tin oxalate, tin chloride, and tin sulfate.

[0048] In some embodiments, in step (1), the carbon source includes at least one of coconut shell charcoal, rice husk charcoal, and straw charcoal, preferably coconut shell charcoal; the carbon source can be obtained by purchase.

[0049] In this embodiment of the invention, coconut shell carbon possesses a loose three-dimensional carbon structure with a large pore volume and specific surface area, exhibiting chemical stability and environmental friendliness. It helps improve ion adsorption capacity, and the addition of coconut shell carbon plays a positive role in the dispersion of metal salts in the ball milling media. Coconut shell carbon also facilitates ion transport. The composite of SnSeS and coconut shell carbon significantly improves the conductivity and structural stability of the material. The buffering effect of coconut shell carbon can alleviate the volume change of SnSeS during charge and discharge processes, reducing material pulverization and thus improving cycle life.

[0050] In some embodiments, in step (1), the molar amount of the tin salt and the mass ratio of the carbon source are (1-5 mmol): (1-5 g), specifically, 1-5 mmol (e.g., 1, 2, 3, 4, 5): 1-5 g (e.g., 1, 1.5, 2, 3, 4, 5);

[0051] In a specific embodiment, the molar amount of the tin salt is 1 to 5 mmol, for example, it can be 1 mmol, 2 mmol, 3 mmol, 4 mmol, or 5 mmol; the mass of the carbon source is 1 to 5 g, for example, it can be 1 g, 1.5 g, 2 g, 3 g, 4 g, or 5 g.

[0052] In this embodiment of the invention, the molar ratio of tin salt to carbon source is (1-5 mmol):(1-5 g). Sufficient carbon source allows the tin salt to adhere more effectively to it, thereby improving its dispersibility and further enhancing the rate performance and cycle performance of the SnSeS / carbon composite material. If the carbon source is too large relative to the total amount of tin salt, it will completely encapsulate the metal salt, reducing the efficiency of ball milling; if the carbon source is too small relative to the total amount of tin salt, the dispersion of the carbon source in the material will be limited, resulting in an incomplete conductive network and affecting electron transport between active materials.

[0053] In some embodiments, in step (1), the solvent includes at least one of water, ethanol, or N,N-dimethylformamide. Optionally, the water is deionized water. The mass-volume ratio of the carbon source to the solvent is 1-5 g: 1-6 mL, specifically, 1-5 g (e.g., 1, 2, 3, 4, 5) : 1-6 mL (e.g., 1, 2, 3, 4, 5, 6). In specific embodiments, the amount of solvent used can be 1-6 mL, specifically, for example, 1 mL, 2 mL, 3 mL, 4 mL, 5 mL, 6 mL.

[0054] In some embodiments, in step (1), tin salt, carbon source, and solvent are mixed and ball-milled; optionally, during the ball milling process, the total mass ratio of the tin salt and carbon source to the mass of the milling beads is 1:(2-60), specifically, 1:2-60 (e.g., 2, 3, 5, 10, 20, 30, 40, 50, 60); the ball milling time is 1-20 hours, specifically, for example, 1 hour, 5 hours, 10 hours, 15 hours, 20 hours; the ball milling speed is 200-600 rpm, specifically, for example, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm; the ball milling is carried out in a ball milling jar. In the embodiments of the present invention, by adjusting the ball milling time, etc., it is beneficial to further control the microstructure and properties of the material.

[0055] In some embodiments, in step (2), the precursor is heat-treated under an inert atmosphere to obtain an intermediate product; optionally, the inert atmosphere includes at least one of nitrogen or argon; the temperature of the heat treatment is 400 to 1000°C, specifically, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 1000°C; the holding time of the heat treatment is 1 to 5 hours, specifically, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours; the heating rate of the heat treatment is 1-3°C / min, specifically, for example, 1°C / min, 2°C / min, 3°C / min; the heat treatment is carried out in a tube furnace.

[0056] In this embodiment of the invention, the heat treatment temperature is 400–1000°C, which is beneficial for promoting the interaction and composite of tin-based materials and carbon materials dispersed at the nanoscale, promoting the formation of cross-linked three-dimensional carbon framework structures, and obtaining the intermediate product Sn metal and carbon composite. If the temperature is too high, it will damage the material structure and reduce the material's performance.

[0057] In some embodiments, in step (3), the intermediate product is heat-treated with a sulfur source and a selenium source under an inert atmosphere to obtain a SnSeS / carbon composite material.

[0058] Optionally, the selenium source includes at least one of selenium powder and selenium dioxide; the sulfur source includes at least one of sulfur powder, thiourea, and thioacetamide.

[0059] Optionally, the mass ratio of the intermediate product to the sulfur source and the selenium source is 1:2 to 5:2 to 5, specifically, 1:2 to 5 (e.g., 2, 3, 4, 5):2 to 5 (e.g., 2, 3, 4, 5);

[0060] Optionally, the temperature of the heat treatment is 300-600℃, specifically, for example, 300℃, 400℃, 500℃, 600℃; the holding time of the heat treatment is 1-3h, specifically, for example, 1h, 2h, 3h; the inert atmosphere includes at least one of nitrogen or argon; the heat treatment is carried out in a tube furnace.

[0061] In this embodiment of the invention, the intermediate product of uniformly dispersed tin-based material at the nanoscale is subjected to heat treatment and vapor-phase selenium sulfidation to obtain SnSeS / carbon composite material. The heat treatment temperature is 300–600℃, which is conducive to the moderate growth of internal grains and the formation of a stable crystal structure. Temperatures that are too high or too low can lead to material structure collapse, phase transformation, or excessive grain coarsening, thus reducing material performance.

[0062] In some embodiments, in step (3), the SnSeS / carbon composite material has a three-dimensional carbon framework structure, and SnSeS particles are distributed inside and on the surface of the three-dimensional carbon framework structure; SnSeS particles are uniformly distributed inside and on the surface of the three-dimensional carbon framework structure; SnSeS particles are uniformly distributed on the surface of the SnSeS / carbon composite material; the particle size of the SnSeS particles is 20-50 nm, specifically, for example, 20 nm, 30 nm, 40 nm, 50 nm.

[0063] In this embodiment of the invention, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS particles distributed inside and on the surface, which helps prevent agglomeration and ensures efficient utilization of active materials. The SnSeS particles have a particle size of 20-50 nm, exhibiting higher electrochemical activity, which is beneficial for improving the specific capacity and charge / discharge efficiency of the material.

[0064] This invention discloses a SnSeS / carbon composite material, which is prepared using the method described in this invention. In this embodiment, the SnSeS / carbon composite material possesses a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on its surface, exhibiting excellent rate performance and a long cycle life.

[0065] This invention discloses an application of a SnSeS / carbon composite material in sodium-ion batteries. In this embodiment, the SnSeS / carbon composite material possesses a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on its surface, exhibiting excellent rate performance and long cycle life, and can be used as a negative electrode material for sodium-ion batteries.

[0066] In some embodiments, it is used as a negative electrode material for sodium-ion batteries.

[0067] An embodiment of the present invention provides an anode material comprising the SnSeS / carbon composite material described in this embodiment. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and long cycle life, and can be used as an anode material.

[0068] An embodiment of the present invention provides a sodium-ion battery comprising the SnSeS / carbon composite material described in this embodiment. In this embodiment, the SnSeS / carbon composite material has a three-dimensional carbon framework structure with SnSeS nanoparticles distributed internally and on the surface, exhibiting excellent rate performance and long cycle life, and can be used in sodium-ion batteries.

[0069] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.

[0070] Example 1

[0071] A method for preparing a SnSeS / carbon composite material includes the following steps:

[0072] (1) Take 4 mmol of tin chloride, 1.5 g of coconut shell charcoal and 2 mL of deionized water and add them to the agate ball milling jar in sequence; add 45 g of agate ball milling beads to the agate ball milling jar; transfer the ball milling jar into a planetary ball mill and complete the assembly, and then perform ball milling for a total time of 5 hours at a speed of 400 rpm to obtain the precursor;

[0073] (2) The precursor was subjected to high-temperature heat treatment under nitrogen atmosphere protection. The temperature was increased to 600℃ at a heating rate of 2℃ / min and then subjected to high-temperature heat treatment for 2h to obtain the intermediate product.

[0074] (3) The intermediate product was heat-treated with sulfur powder and selenium powder at a mass ratio of 1:2:2 at 500°C for 2 hours under a nitrogen atmosphere to obtain SnSeS / carbon composite material (SnSeS / C).

[0075] Figure 1 (a) and (b) are SEM images of the SnSeS / carbon composite material in Example 1. It can be seen that the SnSeS / carbon composite material has a three-dimensional carbon framework structure, and SnSeS particles are uniformly distributed inside and on the surface of the three-dimensional carbon framework structure.

[0076] Figure 2 The XRD pattern of the SnSeS / carbon composite material in Example 1 shows that the SnSeS / carbon composite material contains hexagonal tin selenide sulfide (JCPDS No. 97-065-0864). The broad diffraction peaks around 26° are attributed to amorphous carbon, and the product has good crystallinity, indicating that the SnSeS / carbon composite material was successfully synthesized.

[0077] Example 2

[0078] The method is the same as in Example 1, except that in step (1), coconut shell charcoal is replaced with rice husk charcoal.

[0079] Example 3

[0080] The method is the same as in Example 1, except that in step (1), coconut shell charcoal is replaced with straw charcoal.

[0081] Example 4

[0082] A method for preparing a SnSeS / carbon composite material includes the following steps:

[0083] (1) Take 2 mmol of tin chloride, 3 g of straw charcoal and 2 mL of deionized water and add them to the agate ball milling jar in sequence; add 45 g of agate grinding beads to the agate ball milling jar; transfer the ball milling jar into the planetary ball mill and complete the assembly, and then perform ball milling for a total time of 8 hours at a speed of 300 rpm to obtain the precursor;

[0084] (2) The precursor was subjected to high-temperature heat treatment under nitrogen atmosphere protection, and then heated to 500℃ at a heating rate of 2℃ / min and subjected to high-temperature heat treatment for 3h to obtain the intermediate product.

[0085] (3) The intermediate product was heat-treated with thiourea and selenium dioxide in a mass ratio of 1:3:3 at 300°C for 1 h under a nitrogen atmosphere to obtain SnSeS / carbon composite material.

[0086] Example 5

[0087] A method for preparing a SnSeS / carbon composite material includes the following steps:

[0088] (1) Take 2 mmol of tin sulfate, 3 g of rice husk charcoal and 4 mL of ethanol and add them to the agate ball milling jar in sequence; add 30 g of agate ball milling beads to the agate ball milling jar; transfer the ball milling jar into the planetary ball mill and complete the assembly, and then perform ball milling for a total time of 8 hours at a speed of 600 rpm to obtain the precursor;

[0089] (2) The precursor was subjected to high-temperature heat treatment under nitrogen atmosphere protection, and the temperature was increased to 700℃ at a heating rate of 2℃ / min and then subjected to high-temperature heat treatment for 1h to obtain the intermediate product.

[0090] (3) The intermediate product, thioacetamide, and selenium dioxide were heat-treated at 400°C for 1 hour under a nitrogen atmosphere in a mass ratio of 1:2:2 to obtain SnSeS / carbon composite material.

[0091] Example 6

[0092] A method for preparing a SnSeS / carbon composite material includes the following steps:

[0093] (1) Take 3 mmol of tin oxalate, 6 g of rice husk charcoal and 2 mL of N,N-dimethylformamide and add them to the agate ball milling jar in sequence; add 20 g of agate ball milling beads to the agate ball milling jar; transfer the ball milling jar into a planetary ball mill and complete the assembly, and then perform ball milling for a total time of 6 hours at a speed of 500 rpm to obtain the precursor;

[0094] (2) The precursor was subjected to high-temperature heat treatment under nitrogen atmosphere protection, and the temperature was increased to 600℃ at a heating rate of 2℃ / min and then subjected to high-temperature heat treatment for 3h to obtain the intermediate product.

[0095] (3) The intermediate product was heat-treated with thiourea and selenium powder at a mass ratio of 1:5:5 at 500°C for 1 hour under a nitrogen atmosphere to obtain SnSeS / carbon composite material.

[0096] Comparative Example 1

[0097] The preparation method is the same as that in Example 1, except that sulfur powder is not added in step (3).

[0098] Comparative Example 2

[0099] The preparation method is the same as that in Example 1, except that no selenium powder is added in step (3).

[0100] Comparative Example 3

[0101] A method for preparing a SnSeS / carbon composite material includes the following steps:

[0102] (1) Take 4 mmol of tin chloride, sulfur powder, selenium powder, 1.5 g of coconut shell charcoal and 2 mL of deionized water and add them to the agate ball milling jar in sequence. The amount of sulfur powder and selenium powder is the same as in Example 1. Add 45 g of agate grinding beads to the agate ball milling jar. Transfer the ball milling jar to the planetary ball mill and complete the assembly. Then, perform ball milling for a total time of 5 hours at a speed of 400 rpm to obtain the precursor.

[0103] (2) The precursor was subjected to high-temperature heat treatment under nitrogen atmosphere protection. The temperature was increased to 600℃ at a heating rate of 2℃ / min and then subjected to high-temperature heat treatment for 2h to obtain SnSeS / carbon composite material.

[0104] Comparative Example 4

[0105] The preparation method is the same as that in Example 1, except that in step (1), 6 mmol of tin chloride and 1 g of coconut shell charcoal are used.

[0106] Comparative Example 5

[0107] The preparation method is the same as that in Example 1, except that in step (1), 1 mmol of tin chloride and 6 g of coconut shell charcoal are used.

[0108] Performance testing

[0109] The materials obtained in the examples or comparative examples were mixed and ground with a conductive agent (Super P) and a binder (polyvinylidene fluoride) at a mass ratio of 7:2:1. Then, an appropriate amount of N-methylpyrrolidone was added to prepare a homogeneous slurry. This slurry was then evenly coated onto a current collector (copper foil) using a coater. After drying at 80°C for 12 hours, it was die-cut into electrode sheets with a diameter of 12 mm. Using glass fiber as the separator, sodium foil as the counter electrode, and 1.0 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether as the electrolyte, CR2025 button batteries were assembled in a glove box filled with argon atmosphere and with water and oxygen values ​​both less than 0.01 ppm. After being placed at 25°C for 24 hours, constant current charge-discharge tests were performed using a Newway tester within the range of 0.01–3V.

[0110] Figure 3 The diagram shows the cycling performance of the sodium-ion battery made of the SnSeS / C composite material prepared in Example 1. It achieves a discharge specific capacity of 533 mAh / g after 200 cycles at a current density of 1 A / g, indicating that the SnSeS / carbon composite material has a long cycle life.

[0111] Figure 4The diagram shows the rate performance of the sodium-ion battery based on the SnSeS / C composite material prepared in Example 1. At current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 5 A / g, the reversible specific capacities are 652 mAh / g, 656 mAh / g, 648 mAh / g, 620 mAh / g, 573 mAh / g, and 522 mAh / g, respectively. The SnSeS / carbon composite material exhibits excellent rate performance.

[0112] The rate discharge specific capacity of the examples or comparative examples is shown in Table 1.

[0113] Table 1

[0114]

[0115] As can be seen from Table 1, the SnSeS / carbon composite material prepared by the present invention in Examples 1-6 has excellent rate performance and long cycle life as a negative electrode material for sodium-ion batteries.

[0116] Compared with Examples 1-3, when the carbon source was changed in Examples 2 and 3, the performance of the material at a current of 0.1 A / g to 1 A / g was lower than that of Example 1. This is because coconut shell carbon was used in Example 1. Coconut shell carbon has a large pore volume and specific surface area, which helps to improve the ion adsorption capacity. At the same time, the addition of coconut shell carbon played a positive role in the dispersion of metal salts in the ball milling media. When the carbon source is sufficient, the metal salt can adhere to the carbon source more effectively, thereby improving its dispersibility in the media, and thus improving the dispersibility of SnSeS and improving the rate performance.

[0117] Comparing Example 1 with Comparative Examples 1 and 2, it can be found that the rate performance of the material decreases when no sulfur or selenium source is added. The SnSeS / carbon composite material in Example 1 exhibits excellent rate performance and a long cycle life.

[0118] Comparing Example 1 and Comparative Example 3, it can be found that in Comparative Example 3, the rate performance of the material decreased after all raw materials were mixed, ball-milled, and heat-treated in one step. This is because the dispersion of SnSeS was relatively poor when tin chloride, sulfur powder, selenium powder, and coconut shell carbon were mixed and heat-treated together. In Example 1, tin salt and carbon source were first uniformly composited at the nanoscale by ball milling. The precursor heat treatment promoted the interaction between the tin-based material and the carbon material, optimized the crystal structure and microstructure of the tin-based material, and the intermediate product was heat-treated to perform gas-phase selenium sulfidation to form the SnSeS phase, resulting in a SnSeS / carbon composite material. This improved the dispersion of SnSeS and thus improved the rate performance.

[0119] Comparing Example 1 and Comparative Example 4, it can be found that when the amount of tin salt in Comparative Example 4 is too high, the dispersion of carbon source in the material will be limited, resulting in an incomplete conductive network, affecting the transmission of electrons between active materials, and reducing rate performance.

[0120] Comparative Example 1 and Comparative Example 5 show that excessive carbon source can encapsulate metal salts, hindering the contact and reaction between metal salts. This may lead to changes in the structure and properties of the material, thereby adversely affecting battery performance.

[0121] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0122] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.

Claims

1. A method for preparing a SnSeS / carbon composite material, characterized in that, Includes the following steps: (1) The tin salt, carbon source and solvent are mixed and ball-milled to obtain the precursor; (2) The precursor is heat-treated in an inert atmosphere to obtain an intermediate product; (3) The intermediate product is heat-treated with a sulfur source and a selenium source under an inert atmosphere to obtain a SnSeS / carbon composite material.

2. The method for preparing the SnSeS / carbon composite material according to claim 1, characterized in that, In step (1), the tin salt includes at least one of tin oxalate, tin chloride, and tin sulfate; And / or, the carbon source includes at least one of coconut shell charcoal, rice husk charcoal, and straw charcoal; And / or, the molar amount of the tin salt to the mass ratio of the carbon source is (1-5 mmol): (1-5 g); And / or, the solvent includes at least one of water, ethanol, or N,N-dimethylformamide.

3. The method for preparing the SnSeS / carbon composite material according to claim 1, characterized in that, In step (1), during the ball milling process, the total mass ratio of the tin salt and carbon source to the mass of the milling beads is 1:(2-60); And / or, the ball milling time is 1 to 20 hours; And / or, the ball mill rotates at a speed of 200 to 600 rpm.

4. The method for preparing the SnSeS / carbon composite material according to claim 1, characterized in that, In step (2), the inert atmosphere includes at least one of nitrogen or argon; And / or, the temperature of the heat treatment is 400–1000°C; And / or, the heat treatment holding time is 1 to 5 hours.

5. The method for preparing the SnSeS / carbon composite material according to claim 1, characterized in that, In step (3), the selenium source includes at least one of selenium powder and selenium dioxide; And / or, the sulfur source includes at least one of sulfur powder, thiourea, and thioacetamide; And / or, the mass ratio of the intermediate product to the sulfur source and the selenium source is 1:(2-5):(2-5); And / or, the temperature of the heat treatment is 300–600°C; And / or, the heat treatment holding time is 1 to 3 hours; And / or, the inert atmosphere includes at least one of nitrogen or argon.

6. The method for preparing the SnSeS / carbon composite material according to claim 1, characterized in that, In step (3), the SnSeS / carbon composite material has a three-dimensional carbon framework structure, and SnSeS particles are distributed inside and on the surface of the three-dimensional carbon framework structure; the particle size of the SnSeS particles is 20-50 nm.

7. A SnSeS / carbon composite material, characterized in that, The SnSeS / carbon composite material was prepared by any one of claims 1-6.

8. An application of the SnSeS / carbon composite material according to claim 7, characterized in that, Used in sodium-ion batteries.

9. A negative electrode material, characterized in that, Including the SnSeS / carbon composite material as described in claim 7.

10. A sodium-ion battery, characterized in that, Including the SnSeS / carbon composite material as described in claim 7.